Normas brasileiras de contabilidade aplicadas ao setor público: um estudo sobre a implementação em universidades federais brasileiras - Lilian Tadim Marques (2017)
The purpose of the study was to identify the perception of accountants and directors working in accounting and finance departments (DCF) of federal universities in relation to the Brazilian Accounting Standards Applied to the Public Sector (NBCASP). The research is justified by the importance, both for a society and for managers, to reveal to what extent how universities have been able to adapt to new international accounting standards and the professionals' point of view on changes. It is believed that this work also contributes to a continuous training of the accounting professional, demonstrating how new demands that surround their role in the public sector. As for the methodology, it was an exploratory research, in which the professionals' perception about the implementation of the NBCASP was initially identified. It was also sought to identify an adherence to the new standards through the Adherence Level Index (INA) and a documentary analysis was also carried out using a checklist for the disclosure of accounting information. 53 professionals participated in this study, corresponding to the participation of 41 federal universities, distributed in all Brazilian regions. In the perception of the professionals, as the NBCASP brought to the public sector somewhat for the accounting information as for the recognition of the work of the professionals by its implementation. The results of the study confirm that as NBCASP are in the phase of implementation in the universities and that, for some items, it is not possible to attend due to lack of adequacy of systems or lack of defined methodology. In this sense, it is concluded that the complete NBCASP service is not yet a reality without a public sector to, despite declaring compliance with all norms. In general, a perception of professionals regarding NBCASP is positive, with recognition of advantages for registration and disclosure of information, and demonstrations, by the professionals, for their attendance with useful perspectives on the part of the managers.